Ventral dermatitis in rowi (Apteryx rowi) caused by cutaneous capillariasis. (December 2020) - French, Adrienne F.; Castillo-Alcala, Fernanda; Gedye, Kristene R.; Knox, Matthew A.; Roe, Wendi D.; Gartrell, Brett D.
Abstract: In 2013 there was an outbreak of crusting ventral dermatitis among a group of juvenile rowi ( Apteryx rowi ), a species of the endangered New Zealand kiwi, that were being raised on an off-shore island sanctuary. Biopsies taken at the time found nematodes migrating within the epidermis of affected skin but the specific identity and origin of the organisms was not established, and sporadic cases of similar skin disease continue to occur on the island. On examination of additional sections from the original skin biopsies, adult nematodes and eggs were identified, the histomorphology of which was consistent with Capillaria sensu lato . PCR was performed on DNA extracted from archived formalin-fixed, paraffin-embedded tissue blocks of skin from eight affected rowi, using primers targeting the 18S region of nuclear ribosomal DNA and the COI gene of mitochondrial DNA of capillarid nematodes. The 18S sequences from all rowi samples were identical and matched sequences from members of the genus Eucoleus . In contrast, two distinct capillarid COI sequences were obtained, in one case both from the same rowi skin biopsy. While there were no close matches, both COI sequences also aligned nearest to sequences identified as Eucoleus spp. It is considered unlikely that two different nematode species are involved in the rowi skin lesions and the possible amplification of a COI pseudogene or "numt" is discussed. A species-level identification of the capillarid nematodes causing skin disease in rowi was not obtained, however based on histological evaluation the infections include reproductively-active adult nematodes. This finding indicates the possibility of perpetuation of the skin disease in the absence of the original source, as well as raising potential for the transfer of infection from the island when the juvenile rowi are translocated to their new habitats. Graphical abstract: Image 1 Highlights: Dermatitis associated with nematode migration has been diagnosed in juvenile rowi kiwi. Histological and molecular analysis indicates a member of Capillaria sensu lato . The possible amplification of a COI pseudogene is discussed.